Contemporary Medieval in Practice (University College London, 2019)
Contemporary arts, both practice and methods, offer medieval scholars innovative ways to examine, explore, and reframe the past. Medievalists offer contemporary studies insights into cultural works of the past that have been made or reworked in the present. Creative-critical writing invites the adaptation of scholarly style using forms such as the dialogue, short essay, and the poem; these are, the authors argue, appropriate ways to explore innovative pathways from the contemporary to the medieval, and vice versa. Speculative and non-traditional, The Contemporary Medieval in Practice adapts the conventional scholarly essay to reflect its cross-disciplinary, creative subject. This book 'does' Medieval Studies differently by bringing it into relation with the field of contemporary arts and by making 'practice', in the sense used by contemporary arts and by creative-critical writing, central to it. Intersecting with a number of urgent critical discourses and cultural practices, such as the study of the environment and the ethics of understanding bodies, identities, and histories, this short, accessible book offers medievalists a distinctive voice in multi-disciplinary, trans-chronological, collaborative conversations about the Humanities. Its subject is early medieval British culture, often termed Anglo-Saxon Studies (c. 500-1100), and its relation with, use of, and re-working in contemporary visual, poetic, and material culture (after 1950).